KARDIOCHIRURGIA DOROSŁYCHPatients with aortic stenosis and porcelan aorta – new perspective - Przybylski, Roman; Wilczek, Krzysztof; Chodór, Piotr; Krasoń, Marcin; Niklewski, Tomasz; Głowacki, Jan; Nadziakiewicz, Paweł; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
In 2009 two patients with aortic stenosis and porcelan aorta were terated by transapical TAVI method In Silesian Center for Hart Diseases. Implantations and postoperative period were uneventful. This new method of treatment is the most efficient for these very challenging patients. They are able to come back to their normal live.